Development of Routes for the Stereoselective Preparation of β-Aryl- C-glycosides via C-1 Aryl Enones - Singh A.K.; Kanaujiya V.K.; Tiwari V.; Sabiah S.; Kandasamy J. (My University, 2025)
A wide range of enones derived from d-glucal, d-galactal, l-rhamnal, d-rhamnal, and l-arabinal underwent Heck-coupling with various arylboronic acids bearing electron-donating and -withdrawing groups in the presence of palladium acetate and 1,10-phenanthroline. These reactions provided synthetically useful C-1 aryl enones in good yields. Many sensitive functional groups as well as protecting groups present in arylboronic acids and enones, respectively, remained intact under optimized conditions. The stereoselective hydrogenation of C-1 aryl enones with Pd-C/H2 provides the β-isomer of 2-deoxy-aryl-C-glycosides in excellent yield. The C-1 aryl enones were also used as precursors for the synthesis of 2-hydroxy-β-aryl-C-glycosides. Regioselective C-2 halogenations and vinylations of C-1 aryl enones were achieved in excellent yields. © 2020 American Chemical Society.